Does it Make Sense to Use Scents to Enhance Brand Memory? - Morrin, Maureen; Ratneshwar, S. (Journal of Marketing Research, 2003)
Can pleasant ambient scents enhance consumer memory for branded products? If so, why? The authors examine the effects of ambient scent on recall and recognition of brands in two studies. In the first (i.e., encoding) phase of each study, subjects are asked to evaluate familiar and unfamiliar brands while viewing digital photographs of products on a computer screen; stimulus viewing times are measured covertly on the computer. Ambient scent is manipulated in the experiment room through a diffuser. In the second (i.e., retrieval) phase, conducted 24-hours later, brand recall and recognition accuracy are assessed. In both studies, ambient scent improves both recall and recognition of familiar and unfamiliar brands. This pattern emerges whether or not the scent is congruent with the product category (Study 1), and the enhancement in brand memory is due to the presence of ambient scent during encoding rather than retrieval (Study 2). Although ambient scent apparently did not alter subjects' self-assessed mood or arousal levels, it increased their attention in terms of longer stimulus viewing times. Mediation analyses suggest that the attention mechanism most likely explains why ambient scent improves brand memory.